THE ROLE OF ORGANIZATIONAL CULTURE IN MEDIATION THE INFLUENCE OF COORDINATION, SUPERVISION AND COMMUNICATION FUNCTIONS ON PERFORMANCE OF EMPLOYEES OF THE SECRETARIAT OF THE REGIONAL PEOPLE'S REPRESENTATIVE BOARD OF BULUNGAN REGENCY - Rahmi Jayanti; Ana Srie Kaningsih; Tri Darmayanti; Ruby Ruby (STKIP Singkawang, 2022)
The purpose of the study was to determine the effect of the function of coordination, supervision and communication either directly or indirectly on the performance of ASN at the DPRD Secretariat office in Bulungan Regency after going through organizational culture. This type of quantitative research is descriptive explanatory. Total population and sample are 64 people. Collecting data by distributing questionnaires and continued in the analysis with path analysis. The results of hypothesis testing are proven that the coordination function shows a positive influence on organizational culture. Supervision shows a positive influence on organizational culture. Communication shows a positive influence on organizational culture. The coordination function directly affects employee performance. It shows that the coordination function has a direct significant effect on performance. This means that any increase in the coordination function will improve the performance of employees in carrying out the tasks for which they are responsible. Supervision directly affects employee performance shows that supervision has a direct significant effect on performance. Communication directly affects employee performance, this shows that if communication is increased by one unit, it will directly increase employee performance. Organizational culture has no significant effect on employee performance. The direct influence between the functions of coordination, supervision and communication either partially or simultaneously on the performance of ASN is greater than the indirect effect between the functions of coordination, supervision and communication through organizational culture so that the direct influence is more dominant than the indirect influence.